Stent-assisted coiling of cerebral aneurysms: multi-center analysis of radiographic and clinical outcomes in 659 patients. (17th September 2019) - Mokin, Maxim; Primiani, Christopher T; Ren, Zeguang; Piper, Keaton; Fiorella, David J; Rai, Ansaar T; Orlov, Kirill; Kislitsin, Dmitry; Gorbatykh, Anton; Mocco, J; De Leacy, Reade; Lee, Joyce; et al.
Abstract : Introduction: The endovascular stent-assisted coiling approach for the treatment of cerebral aneurysms is evolving rapidly with the availability of new stent devices. It remains unknown how each type of stent affects the safety and efficacy of the stent-coiling procedure. Methods: This study compared the outcomes of endovascular coiling of cerebral aneurysms using Neuroform (NEU), Enterprise (EP), and Low-profile Visualized Intraluminal Support (LVIS) stents. Patient characteristics, treatment details and angiographic results using the Raymond–Roy grade scale (RRGS), and procedural complications were analyzed in our study. Results: Our study included 659 patients with 670 cerebral aneurysms treated with stent-assisted coiling (NEU, n=182; EP, n=158; LVIS, n=330) that were retrospectively collected from six academic centers. Patient characteristics included mean age 56.3±12.1 years old, female prevalence 73.9%, and aneurysm rupture on initial presentation of 18.8%. We found differences in complete occlusion on baseline imaging, defined as RRGS I, among the three stents: LVIS 64.4%, 210/326; NEU 56.2%, 95/169; EP 47.6%, 68/143; P=0.008. The difference of complete occlusion on 10.5 months (mean) and 8 months (median) angiographic follow-up remained significant: LVIS 84%, 251/299; NEU 78%, 117/150; EP 67%, 83/123; P=0.004. There were 7% (47/670) intra-procedural complications and 11.5% (73/632) post-procedural-related complications in our cohort. Furthermore, procedure-related complications were higher in the braided-stents vs laser-cut, P=0.002. Conclusions: There was a great variability in techniques and choice of stent type for stent-assisted coiling among the participating centers. The type of stent was associated with immediate and long-term angiographic outcomes. Randomized prospective trials comparing the different types of stents are warranted.